2018
DOI: 10.1111/jfb.13867
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of fish hearing

Abstract: Underwater sound is directional and can convey important information about the surrounding environment or the animal emitting the sound. Therefore, sound is a major sensory channel for fishes and plays a key role in many life‐history strategies. The effect of anthropogenic noise on aquatic life, which may be causing homogenisation or fragmentation of biologically important signals underwater is of growing concern. In this review we discuss the role sound plays in the ecology of fishes, basic anatomical and phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 175 publications
(249 reference statements)
0
24
0
Order By: Relevance
“…Putland and Mensinger (2019) showed that acoustic deterrents have generally had greater success deterring species in the order Cypriniformes than the order Perciformes. Much of the variability in the auditory capacity of fishes likely reflects adaptation to different underwater soundscapes (Amoser & Ladich, 2005; Putland et al., 2019). For example, ostariophysian fishes, including many invasive carps, catfishes and Tench ( Tinca tinca ), may be more sensitive to auditory stimuli due to specialised auditory structures that improve hearing in shallow freshwater environments (Popper & Fay, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Putland and Mensinger (2019) showed that acoustic deterrents have generally had greater success deterring species in the order Cypriniformes than the order Perciformes. Much of the variability in the auditory capacity of fishes likely reflects adaptation to different underwater soundscapes (Amoser & Ladich, 2005; Putland et al., 2019). For example, ostariophysian fishes, including many invasive carps, catfishes and Tench ( Tinca tinca ), may be more sensitive to auditory stimuli due to specialised auditory structures that improve hearing in shallow freshwater environments (Popper & Fay, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For those interested in broadening their understanding of general issues of fish bioacoustics (hearing, sound production, behaviour etc . ), there are papers in a volume by Webb et al () as well as several more recent reviews (Ladich, ; Ladich & Fay, ; Mickle & Higgs, ; Putland et al, ). More detailed reviews of potential effects of anthropogenic sound on fishes (and other aquatic animals) can be found in papers by the authors of this review (Hawkins et al, ; Hawkins & Popper, ; Popper & Hawkins, ) and in the reports of several meetings on the Effects of Noise on Aquatic Life (http://www.an-2019.org; Hawkins et al, ; Popper & Hawkins, , and the open access Proceedings of Meetings on Acoustics (http://www.go.umd.edu/UcA).…”
Section: Additional Background Informationmentioning
confidence: 99%
“…There is a need to investigate the hearing abilities of lampreys and many other fishes, under conditions where the particle motion can be monitored or estimated and the ratios of these two potential stimuli can be varied. Such experiments have been reviewed in a number of recent papers, including Hawkins () and Putland et al ().…”
Section: Fish Hearingmentioning
confidence: 99%
“…Sound can convey information directly and be used as a major communication mode in many animals, including fish (Bass & Ladich, 2008; Putland et al., 2019). Some fish can use the swim bladder to produce high level sounds which can be heard at long distances (Alves et al., 2016; Kasumyan, 2008; Montie et al., 2017).…”
Section: Introductionmentioning
confidence: 99%